EFL TEACHERS’ PERCEPTIONS OF MOBILE-ASSISTED LANGUAGE LEARNING INTEGRATION IN VOCABULARY INSTRUCTION - Azimova Muborak (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract While a substantial body of research has examined learners’ engagement with mobile-assisted language learning (MALL), considerably less attention has been paid to how the teachers responsible for implementing these tools actually perceive them. Teachers’ beliefs about a technology’s usefulness, their confidence in using it, and the institutional constraints they operate under are widely recognized as decisive factors in whether classroom technology adoption succeeds or stalls. This study examined EFL teachers’ perceptions of integrating mobile applications into vocabulary instruction, drawing on the Technology Acceptance Model (Davis, 1989), the Technological Pedagogical Content Knowledge framework (Mishra & Koehler, 2006), and Ertmer’s (1999) distinction between first-order and second-order barriers to technology integration. A qualitative-dominant, mixed-methods design was used with 12 EFL teachers at Ixlos International School in Tashkent, combining a short questionnaire with semi-structured interviews, analyzed thematically following Braun and Clarke (2006). Findings suggest that teachers broadly perceived mobile applications as useful for vocabulary reinforcement and learner engagement, but expressed reservations rooted in classroom management concerns, uneven student device access, and uncertainty about how to pedagogically integrate application-based practice with existing curricular demands. The discussion situates these findings within the broader MALL literature and considers implications for teacher training and institutional support in the Uzbekistani EFL context.